Genetic Aspects of Non-Alcoholic Fatty Liver Disease - Pavel O. Bogomolov; Kseniya Yu. Kokina; Aleksander Yu. Mayorov; Ekaterina E. Mishina ("Paediatrician" Publishers LLC, 2019)
Non-alcoholic fatty liver disease (NAFLD) is the most commonly diagnosed hepatopathy. There is an increase in the incidence of NAFLD in the structure of liver diseases in children and adolescents, which is directly related to the increasing prevalence of obesity. The spectrum of liver tissue changes in NAFLD ranges from benign hepatocellular steatosis to non-alcoholic steatohepatitis (NASH), fibrosis, cirrhosis of the liver, and hepatocellular carcinoma. With the increasing prevalence of NAFLD in children, we can expect an increase in the incidence of adverse outcomes among people of working age. The key problem for NAFLD is the prediction of disease outcomes. In epidemiological and genetic studies, the relationship between the morphological stage of NAFLD and hereditary factors is shown. Currently, there are three genes associated with NAFLD (PNPLA3, TM6SF2, and GCKR), which, together with the genes responsible for insulin resistance, lipid deposition, inflammation and fibrogenesis in hepatocytes, determine the phenotype of fatty liver disease. The article considers the modern understanding of the issues of genetics, development of liver steatosis and progression of NASH. It is expected that this knowledge can transform our risk stratification strategies in patients with NAFLD and help identify new therapeutic goals.